Data integration for integrated research and care - Winter, Alfred; Knaup-Gregori, Petra (Methods of information in medicine, 2016)
A national German funding initiative for Medical Informatics focusing at data integration for medicine gives an opportunity to reopen a window to Germany. In the open window appears a best paper selection of the 2015 annual conference of the German Society of Medical Informatics, Biometry and Epidemiology and papers of the German journal GMS Medical Informatics, Biometry and Epidemiology (MIBE). The publications in focus deal with data integration by transferring clinical routine data into an electronic data capture (EDC) system, using natural language processing to make unstructured date processable, measuring quality of record linkage, and by using a unified metadata scheme for integrated documentation in laboratories. Two additional papers present methods for data analysis especially for change point detection in binary sequences and for analyzing categorial data.
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.08.2021